PERANAN FOTO PADA PERWAJAHAN MAJALAH - Prayanto W.H (Imaji, 2007)
Illustration is an important element to support the success of printed media performance, such as magazine. A magazine that consists of only writing without any pictures is boring to the readers. Illustrations in magazines function to help explaining articles, as well as to attract and illustrate the magazines' performance. Therefore, photo journalists' job in taking pictures or recording events around human life is significant to determine the magazines' success visually. Basically to design magazines a solid team work among photographer, designer and editor is absolutely needed to get the best result. No matter how good the pictures are, the visual performance will not be interesting without good design. On the other hand, magazines are not marketable and the articles will not be interesting without attractive pictures. Key words: photography, magazine performance